Governance of Behavioural Biases in Asset Management Industry: Insights from Fund Managers in Malaysia - Zamri Ahmad; Haslindar Ibrahim; Jasman Tuyon (Asian Academy of Management Journal of Accounting and Finance, 2018)
Institutional investors’ behavioural biases have been growingly observed in global financial markets but the governance policy initiatives to mitigate these biases have been long overdue. Taking Malaysia as the case, this paper examines the possibility of behavioural biases among professional investors and discusses the importance of behavioural biases governance in asset management industry. Combination of survey and Delphi methods are used for data collection (survey) and validation of opinions (Delphi). The survey shows the possibility of behavioural biases impacting the thought, decision, and investing strategies of the fund manager. Of great concern, the need to govern behavioural biases in the fund management governance framework has been neglected. This brings challenges to the performance and sustainability of fund management industry. This paper provides behavioural finance insights to inform researchers, practitioners and regulators on the needs and ways to govern behavioural biases through behavioural governance.